Population cross diallel of maize genotypes with varying levels of resistance to the pink stalk borer (Sesamia calamistis: Hampson) and the sugarcane borer (Eldana sacharina: Walker) - Ajala, S.O.; Odiyi, A.C.; The, C.; Olaoye, G (2008)
Genetic diversity that can be profitably exploited is a major desire of several maize (Zea mays L.) breeding programs. The objective of this study was to identify maize populations that could be used in reciprocal recurrent selection programs for combined resistance to two stem borers, Sesamia calamistis: Hampson (the pink stem borer) and Eldana sacharina: Walker (the sugarcane stem borer). Ten maize populations with resistance to Sesamia andor Eldana were used in diallel crosses and the resulting progenies were evaluated in several environments under natural or artificial infestation with one or both of the insect pests. A preponderance of additive gene action was observed for most resistance parameters and agronomic traits while non-additive gene action was responsible for deadheart. The two types of gene action were equally important for stalk breakage and grain yield. Based on both gca and sea effects, three pairs of populations, TZBR Eld 3 x Suwan-1, TZBR-Syn W x DMRLSR-W and TZBR Syn-Y x ATP were identified as suitable candidates for reciprocal recurrent selection programs aimed at improving the levels of resistance to both pests as well as agronomic traits. A pair of reciprocal composites could also be generated from all the populations for future reciprocal recurrent selection efforts.